Penguatan Kapasitas Kelembagaan Kecamatan dalam Meningkatkan SDM untuk Pelayanan Publik di Kecamatan Rambutan-Banyuasin - Budi Aziz; Mohamad Firdaus (Universitas 17 Agustus 1945 Semarang, 2025)
This study examines the importance of strengthening institutional capacity at the sub-district level to improve the quality of human resources (HR) among government officials in order to enhance public service delivery in Banyuasin Regency. As the frontline in the implementation of public services, sub-districts play a crucial role due to their direct interaction with the community. The main issue in this research is the low effectiveness of public services caused by limited institutional capacity and inadequate human resource competencies at the sub-district level. This study employs a descriptive qualitative approach using a case study method focused on Rambutan Sub-district. The theoretical framework includes institutional capacity theory, New Public Management (NPM), and New Public Service (NPS). The research findings indicate that developing institutional capacity through human resource training and the application of modern management practices has a positive impact on service quality. Changes in public service delivery largely depend on the sub-district’s ability to maximize the empowerment of its personnel.